Edukasi Kesehatan Dalam Upaya Menurunkan Kejadian Leptospirosis di Puskesmas Kasihan II, Bantul, Yogyakarta - Tri Sulistyowati; Bella Syafitri Dwi Nurjanah; Octavia Nurin Hamidah; Reniyatun; Hanifah Zulfa Nur Istiqomah; Maria Kartika Sari; Fauziah Savitri; Devi Septyaningsih; Wahdini; Siti Mariyah Salsabilah (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Leptospirosis is a disease of animal origin (zoonosis) that is widespread throughout the world. Leptospirosis is caused by spiral bacteria from the genus Leptospira which can infect animals and humans. Leptospirosis cases were found in several locations in the Special Province of Yogyakarta (DIY), including in Kulonprogo, Sleman and Bantul Regencies. The Bantul District Health Office, DI Yogyakarta, recorded 37 cases of leptospirosis during 2023. Of these, 6 of them died. The purpose of this service is to increase public knowledge at the Kasihan II Health Center about Leptospirosis. The target of this service is the community in the Bantul Regency area. The method used in this research is the lecture method, Audio Visual Aids (AVA) and leaflets. The number of participants in this service is 25 people. The results showed that the respondents' knowledge about Leptospirosis before being given health education was low, namely as many as 20 respondents (80%), while the knowledge of respondents after being given health education was high, namely, as many as 18 respondents (72%) and obtained a P-Value of 0.040 (<0.05) . So it can be concluded that there was an increase in respondents' knowledge after health education was carried out.